Transforming the organization - Gouillart, Francis J.; Kelly, James N. (James Newell), 1940- (New York : McGraw-Hill, 1995)
Drawing on decades of combined experience in helping major companies turn themselves around, the authors use real stories that guide the reader through "hard" disciplines such as shareholder value analysis and activity-based costing, and through "soft" disciplines such as team-building, visioning, and individual renewal. Chapter by chapter, the reader tracks the analytical and emotional progress of a real CEO from a well-known company in the midst of transformation, as well as the wrenching experience of a production scheduler swept up in the transformation process. The authors make a compelling case for viewing the corporation not as a soul-less machine made up of discrete, replaceable parts, but as a living organism - the biological corporation - complete with mind, body, and spirit requiring comprehensive treatment, not organ-by-organ surgery, to ensure overall health.
Gouillart and Kelly lay out the holistic approach of business transformation in a four-part framework: reframing the company's conception of what it is, and what it can achieve; restructuring the corporate body to bring it to a competitive level of performance; revitalizing the company's relationship to the competitive environment, igniting growth in existing businesses and inventing new ones; renewing individuals and the organization, enabling them to become integral parts of a connected and responsible world community.
Introduction: A Framework for Transformation -- Ch. 1. Achieving Mobilization -- Ch. 2. Creating the Vision -- Ch. 3. Building the Measurement System -- Ch. 4. Constructing an Economic Model -- Ch. 5. Configuring the Physical Infrastructure -- Ch. 6. Redesigning the Work Architecture -- Ch. 7. Achieving Market Focus -- Ch. 8. Inventing New Businesses -- Ch. 9. Changing the Rules Through Information Technology -- Ch. 10. Developing the Rewards System -- Ch. 11. Building Individual Learning -- Ch. 12. Developing the Organization.
Includes index.
Keywords: Organizational change; Organizational innovation